In situ autologous growth of self-supporting NiFe-based nanosheets on nickel foam as an efficient electrocatalyst for the oxygen evolution reaction. Issue 38 (12th July 2019) - Wang, Jianying; Teng, Xue; Niu, Yanli; Guo, Lixia; Kong, Jianfei; He, Xiaoming; Chen, Zuofeng
Abstract : We report here a simple and cost-effective autologous growth method to prepare a NiFe-based integrated electrode for efficient electrocatalytic water oxidation. Abstract : A highly efficient and low-cost oxygen evolution reaction electrocatalyst is essential for water splitting. Herein, a simple and cost-effective autologous growth method is developed to prepare NiFe-based integrated electrodes for water oxidation. In this method, a Ni(OH)2 nanosheet film is first developed on nickel foam by oxidative deposition in a chemical bath solution. The as-prepared nanosheet electrode is then immersed into a solution containing Fe(iii ) cations to form an Fe-doped Ni(OH)2 electrode by utilization of the different solubility of metal cations. Benefiting from its unique and integrated nanostructure, this hierarchically structured electrode displays extremely high catalytic activity toward water oxidation. In 1 M KOH, the electrode can deliver a current density of 1000 mA cm −2 at an overpotential of only 330 mV. This work provides a facile way to produce an efficient, durable, and Earth-abundant OER electrocatalyst with no energy input, which is attractive for large-scale water splitting.